Primary School Children's Health Behaviors, Attitudes, and Body Mass Index After a 10-Week Lifestyle Intervention With Follow-Up - Brown, Elise C.; Buchan, Duncan S.; Drignei, Dorin; Wyatt, Frank B.; Kilgore, Lon; Cavana, Jonathan; Baker, Julien S. (Frontiers in Pediatrics, 2018)
Background: Given the current global child obesity epidemic, testing the effectiveness of interventions in reducing obesity and its influencers is paramount. The purpose of this study was to determine immediate and long-term changes in body mass index and psychosocial variables following a 10-week lifestyle intervention. Methods: Seven hundred and seventy participants (8.75 ± 0.98 years of age, 379 boys and 391 girls) took part in the study. Participants had height, weight, and psychosocial questionnaires assessed at pre- and post-control, pre- and post-intervention, and 6-months post-intervention. Participants completed a weekly 10-week intervention consisting of healthy eating and physical activity education, physical activity, parental involvement, and behavior change techniques. Regression models were fit with correlated errors where the correlation occurred only between time points, not between subjects, and the nesting effects of school and area deprivation were controlled. Results: Regression models revealed a significant decrease in body mass index from pre- to post-intervention of 0.8512 kg/m2 (P=0.0182). No Changes in body mass index occurred from post-intervention to 6-month follow-up (P=0.5446). The psychosocial variables did not significantly change. Conclusions: This lifestyle intervention may be an effective means for improving body mass index in primary school children in the short-term if the duration of the intervention is increased, but these changes may not be sustained without on-going support.